Recent Advances in Ionic Liquid-Modified Graphene Oxide as A QuEChERS Compatible Sorbent for Pharmaceutical Analysis of Water Samples - Yusof, Raihana Mohd; Othman, Nurzaimah Zaini; Hanapi, Nor Suhaila Mohamad; Kamaruzaman, Sazlinda; Mahmood, Wan Asyraf Wan; Anis, Ahmad Lutfi (Trends in Sciences, 2025)
Dispersive micro-solid phase extraction (D-µ-SPE), particularly in the form of QuEChERS (quick, easy, cheap, effective, rugged, and safe), has emerged as a leading analytical method due to its minimal solvent use and high extraction efficiency. This review focuses on the application of ionic liquid-modified graphene oxide (IL-GO) as an advanced QuEChERS-compatible sorbent for pharmaceutical analysis in aqueous environments. The incorporation of ionic liquids (ILs) into GO enhances sorbent performance through synergistic interactions such as π-π stacking, hydrogen bonding, and electrostatic attraction have been described. Both covalent and non-covalent functionalization strategies are explored, along with their respective strengths, limitations, and stability. Parameters including pH, temperature, IL loading, and contact time are discussed in relation to extraction efficiency. This review also outlines the relevance of IL-GO to green chemistry and challenges in the application of IL-GO nanosorbents such as IL leaching and toxicity. Future directions include the use of covalently bound and biocompatible ILs to enhance sustainability and analytical reliability. IL-GO sorbents represent a promising highly efficient, green analytical method in environmental monitoring. HIGHLIGHTS The application of dispersive micro solid phase extraction (D-µ-SPE), particularly as a QuEChERS method is described. The recent advances in IL/GO in D-µ-SPE for pharmaceutical analysis of water samples are summarized. The outstanding performance of ionic liquid modified graphene oxide towards pharmaceuticals elimination is due to its good adsorption efficiency, hydrophilicity, stability and reusability are discussed. Factors Affecting Extraction Efficiency by IL-GO is described Further improvement of Ionic Liquid-Modified Graphene Oxide nanosorbents are suggested and discussed. GRAPHICAL ABSTRACT